CHALLENGES IN ENFORCING HATE SPEECH LAWS IN INDONESIAN POLITICS - Diego Romario De Fretes; Asriadi Zainuddin; Darmawati; Muhammadong; Putri Maha Dewi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
Enforcing hate speech laws in Indonesian politics has posed significant challenges in the past. These challenges have impeded the effective implementation of legal measures designed to address hate speech and ensure a fair and inclusive political environment. One of the key challenges was the need for a clear and comprehensive legal framework. Historically, hate speech laws in Indonesia were criticized for being vague and open to interpretation, leading to inconsistent application and potential bias in enforcement. The absence of specific guidelines and criteria for identifying hate speech hindered the prosecution process. Political pressures and biases also posed significant obstacles to enforcing hate speech laws. The influence of political affiliations and interests often interfered with objective decision-making, leading to selective enforcement or leniency based on political considerations. This compromised the impartiality and independence of the enforcement process. Moreover, limited capacity and training among law enforcement agencies and judicial institutions created further hurdles. There needs to be more understanding of hate speech issues, lack of expertise in investigating and prosecuting such cases, and inadequate resources hampering the effective implementation of hate speech laws. These challenges in enforcing hate speech laws in Indonesian politics have hindered the protection of fundamental rights, fostered polarization, and undermined the inclusive nature of the political discourse. Addressing these challenges requires comprehensive legal reforms, capacity building for law enforcement and judicial institutions, and strategies that effectively tackle hate speech in the digital realm.